Design of a Superconducting Nanowire Single-Photon Detector With Dual-Broadband and High Detection Efficiency - Fan Zheng; Ruiying Xu; Yajun Chen; Guanghao Zhu; Biaobing Jin; Lin Kang; Weiwei Xu; Jian Chen; Peiheng Wu (IEEE Photonics Journal)
In this paper, we propose a structure of a superconducting nanowire single-photon detector (SNSPD) with a composite cavity. Compared with the SNSPD in previous studies, our device exhibits a property of high efficiency and dual broadband. Based on the transmission line theory, the structure is abstractedly expressed as an equivalent circuit model and a design method is presented. Taking $λ \,= \,{\rm{1310\,nm}}$ and $λ \,= \,{\rm{1550\,nm}}$ as an example, the structural parameters are calculated and verified by commercial software FDTD Solutions. The simulation results show that peaks of the absorption curve appear at both wavelengths and peak values are all larger than 97.5%. The influence of the upper half cavity on the full width at half maximum (FWHM) of the absorption peak is discussed. Our works provide a reference for designing an SNSPD with different FWHM.